PENGARUH INDEKS BURSA GLOBAL DAN VARIABEL MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) PRIODE 2018-2020 - Agus Salihin Salihin (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2021)
This study aims to determine the effect of the Dow Jones Index, Nikkei 225, Hang Seng, Inflation and Exchange Rates on the Composite Stock Price Index (CSPI). This research includes quantitative research with secondary data types in the form of time series with a sample of 32 months, namely January 2018 to August 2020. The data analysis technique uses multiple linear regression analysis techniques. Based on the results of the study it can be explained that partially the Dow Jones Index, Nikkei 225 and Hang Seng have a significant positive effect on the Composite Stock Price Index (IHSG) for the 2018-2020 period. While inflation and the exchange rate did not have a positive effect on the 2018-2020 Composite Stock Price Index (CSPI). The simultaneous Dow Jones Index, Nikkei 225, Hang Seng, Inflation and Exchange rates have a positive significant effect on the Composite Stock Price Index (IHSG) for the period of 2018-2020. From the results of the analysis of the coefficient of determination of the Dow Jones Index, Nikkei 225, Hang Seng, Inflation and Exchange rates can affect the Composite Stock Price Index (CSPI) of 80%.